Pembuatan dan Pengujian Mesin Pemotong Lidi Tusuk Sate - Gusri Akhyar Ibrahim; Arinal Hamni; Wahyu Budiono (Universitas Mathla'ul Anwar Banten, 2019)
MAKING AND TESTING OF SKEWERS CUTTING MACHINES. In Indonesia there are more than 100 types of bamboo that can be used by craftsmen, one of which is skewers. Skewers are promising commodities for business opportunities. The process of producing skewers are started from cutting down the bamboo, cutting bamboo, splitting bamboo, shriveling bamboo to become a stick skewer after that is done cutting the skewer sticks, drying sticks, polishing the sticks skewers and chopping sticks. The process of cutting a stick skewer which is done at this time is still using a simple tool, so the results are bad and the cutting time is very long. To maintain the quality of the results of a good stick skewer sticks and to increase the productivity of the stick skewers, the process of producing and testing of a skewer stick cutting machine is done. The method to produce a skewer stick cutting machine is done by designing the tool, determining the material to be used then making it. This skewer stick cutting machine is made with a press system and vertical cutting directions. From the results of testing the skewer stick cutting machine obtained that the quality of skewer cutting is good and the time required to cut is only 10 seconds. the difference is about 50 seconds faster than the hand saws used, so as to increase the productivity of the skewer sticks. The cutting machine was impelemented at home industry at Sidomulyo of South Lampung. Using the machine has increased productity and also quality of skewers.